2021
DOI: 10.1108/lodj-10-2020-0458
|View full text |Cite
|
Sign up to set email alerts
|

Protean career attitude and organisational commitment in learning organisation climate

Abstract: PurposeThis study aims to identify the relationship between protean career attitude (PCA) and organisational commitment (OC) in a learning organisation (LO) climate. The study also identified whether negative relationships exist between the structure dimension of LO (SDLO) and PCA, and between PCA and OC, and whether such relationships can be moderated by the people dimension of LO (PDLO).Design/methodology/approachData collected from 305 employees of 26 firms were analysed using the PROCESS macro for SPSS.Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The confirmatory factor analysis (Table 2) shows that the dimensional structure of these concepts is valid even in a non-western context. However, no significant relationship between protean and boundaryless career attitudes and organizational commitment was found [60][61][62][63]. No significant effects were observed on the dimensions of organizational commitment (AC, NC and CC) due to protean career attitudes (SD and VD).…”
Section: Resultsmentioning
confidence: 99%
“…The confirmatory factor analysis (Table 2) shows that the dimensional structure of these concepts is valid even in a non-western context. However, no significant relationship between protean and boundaryless career attitudes and organizational commitment was found [60][61][62][63]. No significant effects were observed on the dimensions of organizational commitment (AC, NC and CC) due to protean career attitudes (SD and VD).…”
Section: Resultsmentioning
confidence: 99%
“…The embedded system refers to the mechanism through which organisations acquire, retain, and disseminate information, skills, and practises across various levels of management (Hannachi, 2016;Hussein et al, 2016;Wang, 2020). Embedded systems play a vital role in aiding the procurement and promulgation of knowledge, enabling people to efficiently access and get the necessary information at any given time (Oh & Koo, 2021). The possession of employee knowledge is of utmost importance for businesses as it enables them to sustain a competitive advantage vis-à-vis their competitors (Zammit et al, 2017).…”
Section: Embedded Systemsmentioning
confidence: 99%
“…Gubler et al (2014) redefine the protean career measure consisting of the concepts of protean career, protean career orientation, and protean career path. However, the often used measurement is the protean career attitude scale (Waters et al, 2014;Babalola & Bruning, 2015;Rahim & Siti-rohaida, 2015), which comprises dimensions driven by self-values and self-direction (Ayoobzadeh, 2021;Oh & Koo, 2021) their strategies to navigate job search, especially in turbulent times, are unknown. To address this gap, the author hypothesized and examined a sequential mediation model whereby freelancer protean career orientation (PCO; Abessolo et al, 2017;Steiner et al, 2019) we found that the three approaches had the following similarities: (1) referring to the initial definition of the Protean Hall career in 1976; (2) use the exact two sizes, namely driven by self-value and self-direction, which is a cognitive component and behavior as a component forming attitude;…”
Section: Conceptualization Of 'New' Protean Careerattitudementioning
confidence: 99%